Child marriage and associated outcomes in northern Ghana: a cross-sectional study - Richard de Groot (BMC Public Health, 2018)
Abstract Background Child marriage is a human rights violation disproportionately affecting girls in lower- and middle-income countries and has serious public health implications. In Ghana, one in five girls marry before their 18th birthday and one in 20 girls is married before her 15th birthday. This paper uses a unique dataset from Northern Ghana to examine the association between child marriage and adverse outcomes for women among a uniquely vulnerable population. Methods Baseline data from on ongoing impact evaluation of a government-run cash transfer programme was used. The sample consisted of 1349 ever-married women aged 20–29 years from 2497 households in the Northern and Upper East regions of Ghana. We estimated a series of ordinary least squares (OLS) and logistic regression models to examine associations of child marriage with health, fertility, contraception, child mortality, social support, stress and agency outcomes among women, controlling for individual characteristics and household-level factors. Results Child marriage in this sample was associated with increased odds of poorer health, as measured by difficulties in daily activities (OR = 2.08; CI 1.28–3.38 among women 20–24 years and OR = 1.58; CI 1.19–2.12 among women 20–29 years), increased odds of child mortality among first-born children (OR = 2.03; CI 1.09–3.77 among women 20–24 years) and lower odds of believing that one’s life is determined by their own actions (OR = 0.42; CI 0.25–0.72 among women 20–24 years and OR = 0.54; CI 0.39–0.75 among women 20–29 years). Conversely, child marriage was associated with lower levels of reported stress (regression coefficient = − 1.18; CI -1.84–-0.51 among women 20–29 years). Conclusions Child marriage is common in Northern Ghana and is associated with poor health, increased child mortality, and low agency among women in this sample of extremely poor households. While not much is known about effective measures to combat child marriage in the context of Ghana, programmes that address key drivers of early marriage such as economic insecurity and school enrolment at the secondary level, should be examined with respect to their effectiveness at reducing early marriage. Trial registration: Registered in the Registry for International Development Impact Evaluations (RIDIE) on 01 July 2015, with number RIDIE-STUDY-ID-55942496d53af.